A new practical robust control of cable‐driven manipulators using time‐delay estimation. (16th April 2019) - Wang, Yaoyao; Yan, Fei; Zhu, Kangwu; Chen, Bai; Wu, Hongtao
Summary: In this paper, a new practical robust control scheme is proposed and investigated for the cable‐driven manipulators under lumped uncertainties. There are three parts in the proposed method, ie, a time‐delay estimation (TDE) part, a modified super‐twisting algorithm (STA) part, and a fractional‐order nonsingular terminal sliding mode (FONTSM) error dynamics part. The TDE uses intentionally time‐delayed system signals to estimate the lumped dynamics of the system and ensures an attractive model‐free control structure. The STA is applied to guarantee high performance and chattering suppression simultaneously in the reaching phase. The FONTSM error dynamics is utilized to obtain fast convergence and strong robustness in the sliding mode phase. Thanks to the above three parts, the proposed control scheme is model free and can ensure high control performance under lumped uncertainties. The stability considering the FONTSM error dynamics and modified STA scheme is analyzed. Comparative simulation and experiments were conducted to demonstrate the effectiveness and superiorities of the newly proposed control scheme. Corresponding experimental results show that our newly proposed control scheme can provide more than 20% improvement of the steady control accuracy under three different reference trajectories.